A Novel Nanoprobe Based on Core–Shell Au@Pt@Mesoporous SiO2 Nanozyme With Enhanced Activity and Stability for Mumps Virus Diagnosis - Long, Lin; Cai, Rui; Liu, Jianbo; Wu, Xiaochun (Frontiers in Chemistry, 2020)
Core-shell structures of nanoporous materials have received a lot of attention in recent years owing to the great versatility of the combined functionalities of cores and shells and their potential application in catalysis and biological applications. In this work, a facile method has been developed to synthesize uniform Au@Pt@mesoporous SiO2 nanostructures with highly peroxidase-like activity, which had a well-defined core–shell structure with Au@Pt nanorod as core and mesoporous SiO2 as a shell. The open mesopores can not only provide convenient transmission channels but also offer a huge location for accommodation of large molecules, such as antibodies and antigens. Here a novel nanoprobe based on Au@Pt@mesoporous SiO2 nanozyme modified with mumps antigens was reported. Specifically, the encapsulation of Au@Pt nanorod in mesoporous SiO2 shell was able to hinder the interaction between catalytical nanoparticles and recognition antigens, retaining the catalytic activity of the inner active nanoparticle core. Furthermore, this nanoprobe exhibited an extraordinarily stability and showed excellent activity. As a result, we presented an enzyme linked immunosorbant assay (ELISA) for the diagnosis of mumps virus; this proposed method exhibited good sensitivity to mumps-specific IgM antibodies. The detection limit can be as low as 10ng/mL, an increase in sensitivity of three orders of magnitude compared to the conventional immunoassay. Our results indicated that this nanoprobe hold great promise with opportunities for applications of biosensors, catalysis and biotechnology.